Penerapan Digital Marketing dalam Pemasaran Produk Sale Pisang Madu Lestari Pacitan Ditinjau dari Ekonomi Islam - Diana Dwi Suryani; Catur Wahyono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In today's era, the development of the business world is growing very rapidly. With the development of the business world, business actors must also develop their businesses by implementing digital marketing. Thus, this study aims to examine a comprehensive analysis of how application digital marketing practices are implemented in marketing sale pisang madu Lestari Pacitan which have been managed by the business owner himself. This study will also review the application of aspects of digital marketing through the lens of Islamic economics. This research employed a qualitative design with descriptive focus. This is undertaken by directly observing, interviewing and observing the product owner. Findings indicate that the marketing efforts implemented by Lestari Pacitan is to create content in the form of videos or photos that are uploaded to social media (WhatsApp, Instagram,Tiktok) and marketplaces (Shopee). Viewed from an Islamic economic perspective, digital marketing applied to the sale pisang product aligns with Islamic economic values, particularly the doctrines of justice, honesty, and transparency. The application of digital marketing to sale pisang madu produksi Lestari Pacitan has succeeded in significantly increasing marketing and sales and providing a positive economic and social impact on other business actors. The implementation of good branding and proper packaging also supports business continuity according to sharia principles. This study provides recommendations to strengthen digital marketing education based on Islamic values ​​to increase competitiveness with sale pisang madu businesses in Pacitan.